Mammary analogue secretory carcinoma of the salivary gland with NTRK fusions: new approaches for diagnostics and targeted therapy (review) - A. V. Ignatova; A. M. Mudunov; S. О. Podvyaznikov; Yu. V. Alymov (Опухоли головы и шеи)
Mammary analogue secretory carcinoma (MASC) of the salivary gland is a rare salivary cancer, histologically resembling to secretory carcinoma of the breast. In 2017 World Health Organization reported MASC is a new salivary cancer subtype. The aim of this article is to collect and analyze data about MASC, particularly clinical, histological and molecular profile, to evaluate targeted therapy effects. We discuss a case report of dramatic and durable response with entrectinib and the development of acquired resistance in an NTRK3-fusion positive salivary cancer, detected by next-generation sequencing. Next-generation sequencing as a comprehensive molecular profiling, that helps to investigate molecular profile of rare tumors and gives an opportunity to use an effective therapeutic options. Identifying ETV6-NTRK3 positive MASC provides a better prognosis for metastatic disease by using a novel effective targeted therapy with tyrosine kinase inhibitors (entrectinib, larotrectinib). Despite a durable and dramatic response, we showed an interesting case of the development of acquired resistance to tyrosine kinase inhibitors mediated by the appearance of a novel NTRK3 G623R mutation. Finally, we believe in great perspectives of comprehensive molecular profiling and targeted therapy for rare malignancies with NTRK gene fusions, including second-generation tyrosine kinase inhibitors.